Association of serious adverse events with Cheyne–Stokes respiration characteristics in patients with systolic heart failure and central sleep apnoea: A SERVE‐Heart Failure substudy analysis. Issue 3 (20th June 2019) - Javed, Faizan; Tamisier, Renaud; Pepin, Jean‐Louis; Cowie, Martin R.; Wegscheider, Karl; Angermann, Christiane; d'Ortho, Marie‐Pia; Erdmann, Erland; Simonds, Anita K.; Somers, Virend K.; Teschler, Helmut; Levy, Patrick; et al.
ABSTRACT: Background and objective: Increases in Cheyne–Stokes respiration (CSR) cycle length (CL), lung‐to‐periphery circulation time (LPCT) and time to peak flow (TTPF) may reflect impaired cardiac function. This retrospective analysis used an automatic algorithm to evaluate baseline CSR‐related features and then determined whether these could be used to identify patients with systolic heart failure (HF) who experienced serious adverse events in the Treatment of Sleep‐Disordered Breathing with Predominant Central Sleep Apnea by Adaptive Servo Ventilation in Patients with Heart Failure (SERVE‐HF) substudy. Methods: A total of 280 patients had overnight diagnostic polysomnography data available; an automated algorithm was applied to quantify CSR‐related features. Results: Median baseline CL, LPCT and TTPF were similar in the control ( n = 152) and adaptive servo‐ventilation (ASV, n = 156) groups. In both groups, CSR‐related features were significantly longer in patients who did ( n = 129) versus did not ( n = 140) experience a primary endpoint event (all‐cause death, life‐saving cardiovascular intervention or unplanned hospitalization for worsening HF): CL, 61.1 versus 55.1 s ( P = 0.002); LPCT, 36.5 versus 31.5 s ( P < 0.001); TTPF, 15.20 versus 13.35 s ( P < 0.001), respectively. This finding was independent of treatment allocation. Conclusion: Patients with systolic HF and central sleep apnoea who experienced serious adverse events had longer CSR CL, LPCT and TTPF. Future studies should examine an independent role for CSR‐related features to enable risk stratification in systolic HF. Abstract : Analysis of the Treatment of Sleep‐Disordered Breathing with Predominant Central Sleep Apnea by Adaptive Servo Ventilation in Patients with Heart Failure (SERVE‐HF) substudy found that patients with systolic heart failure who experienced serious adverse events during the trial had longer Cheyne–Stokes respiration (CSR)‐related characteristics at baseline. These findings suggest that CSR‐related events could be used to define central sleep apnoea phenotypes for future risk stratification. See related Editorial